Assessing Contact Graph Routing Performance and Reliability in Distributed Satellite Constellations. (4th July 2017) - Fraire, J. A.; Madoery, P.; Burleigh, S.; Feldmann, M.; Finochietto, J.; Charif, A.; Zergainoh, N.; Velazco, R.
Abstract : Existing Internet protocols assume persistent end-to-end connectivity, which cannot be guaranteed in disruptive and high-latency space environments. To operate over these challenging networks, a store-carry-and-forward communication architecture called Delay/Disruption Tolerant Networking (DTN) has been proposed. This work provides the first examination of the performance and robustness of Contact Graph Routing (CGR) algorithm, the state-of-the-art routing scheme for space-based DTNs. To this end, after a thorough description of CGR, two appealing satellite constellations are proposed and evaluated by means of simulations. Indeed, the DtnSim simulator is introduced as another relevant contribution of this work. Results enabled the authors to identify existing CGR weaknesses and enhancement opportunities.